(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
The two DUOX enzymes were originally identified as participating in the production of hydrogen peroxide as a pre-requisite for thyroid hormone biosynthesis in the thyroid gland [6]. NOX enzymes function to catalyse the reduction of molecular oxygen to superoxide and various other reactive oxygen species (ROS). They are subunits of the NADPH oxidase complex.